Nanoformulation of Talazoparib Delays Tumor Progression and Ascites Formation in a Late Stage Cancer Model - Baldwin, Paige; Ohman, Anders W.; Medina, Jamie E.; McCarthy, Eric T.; Dinulescu, Daniela M.; Sridhar, Srinivas (Frontiers in Oncology, 2019)
Talazoparib, a potent PARP inhibitor, induces synthetic lethality in BRCA-deficient cancers making it an attractive candidate for ovarian cancer treatment. However, its potency lends itself to side effects associated more closely with traditional chemotherapeutics than other clinically approved PARP inhbitors. We sought to formulate Talazoparib in a nanoparticle delivery system, which allows the drug to be administered intraperitoneally. This was done to specifically target peritoneal dissemination of late stage metastatic ovarian cancer and increase talazoparib’s therapeutic efficacy while minimizing toxic side effects. NanoTalazoparib was developed and characterized with regard to its size, loading, and surface charge. Talazoparib and NanoTalazoparib were tested on a panel of murine and human BRCA cell lines and the dose response was compared to Olaparib’s, the currently used PARP inhibitor. Therapeutic efficacy was tested in vivo in a Brca peritoneal cancer model that mimics late stage disseminated disease. NanoTalazoparib has a diameter of about 70 nm with a neutral surface charge and 75% encapsulation efficiency, which slowly releases the drug over several hours. Dose response analysis indicated that the murine cell lines with conditional BRCA1/2, PTEN, and TP53 deletions had the lowest IC50s. NanoTalazoparib administered on a schedule of three doses weekly slowed disease progression and resulted in significantly less mice with ascites at the end point compared to controls. These results indicate that the slow release nanoformulation, NanoTalazoparib, effectively delivers PARP inhibitor therapy to the peritoneal cavity for disseminated cancer treatment. The ability to decrease ascites formation with the introduction of intraperitoneal NanoTalazoparib suggests this treatment may be an effective way to treat ovarian cancer-associated ascites and slow disease progression.